Intolerance of uncertainty heightens negative emotional states and dampens positive emotional states - Morriss, Jayne; Goh, Kimberly; Hirsch, Colette R.; Dodd, Helen F. (Frontiers in Psychiatry, 2023)
Individuals high in self-reported Intolerance of Uncertainty (IU) tend to view uncertainty as unbearable and stressful. Notably, IU is transdiagnostic, and high levels of IU are observed across many different emotional disorders (e.g. anxiety, depression). Research has primarily focused on how IU evokes and modulates emotional states such as fear and anxiety. However, recent research suggests that IU may have relevance for a broader range of emotional states. Here, an online survey was conducted to examine whether IU evokes and modulates a range of negative (e.g. fear/anxiety, sadness/upset, anger/frustration, disgust) and positive (e.g. happiness/joy, excitement/enthusiasm, surprise/interest) emotional states. Findings within a community sample (n = 231) revealed that individuals with higher levels of IU report: (1) that uncertainty in general and uncertainty under ambiguity are more likely to evoke negative emotional states and less likely to evoke positive emotional states, (2) that uncertainty under risk is less likely to evoke positive emotional states, and (3) that uncertainty heightens existing negative emotional states and dampens existing positive emotional states. Importantly, these IU-related findings remained when controlling for current experiences of general distress, anxious arousal, and anhedonic depression. Taken together, these findings suggest that IU is involved in evoking and modulating a wide array of emotional phenomena, which likely has relevance for transdiagnostic models and treatment plans for emotional disorders.